COVID-19 and Acute Cholecystitis Management: A Systematic Review of Current Literature - Stavridis, Konstantinos; Liosis, Ioannis; Konstantinidis, Michael K.; Kondylis, Georgios; Ioannidis, Argyrios (Frontiers in Surgery, 2022)
Introduction: Since the beginning of the COVID-19 pandemic, many patients with clinically acute presentations have been approached differently. The fear for viral transmission along with the short period of study made patients delay their hospital visits and doctors to reassess the approach of certain acute situations. This study aimed to assess the changes in the management of patients with acute cholecystitis before and during COVID-19. Methods: A systematic review of the literature using PubMed (Medline), Scopus and ScienceDirect databases was performed until 01 September 2021. Two kinds of studies were included, those assessing the management of acute cholecystitis during COVID-19 and those comparing periods before and during the pandemic. The outcomes recorded include management approaches, complications and mean length of stay. Results: Fifteen eligible articles were included in the study. During the pandemic, six studies revealed a shift towards conservative management of acute cholecystitis and five of them reported that conservative management was opted in 73% of the patients. On the contrary, data from all studies revealed that surgical approach was preferred in only 29.2% of patients. Furthermore, when comparing the periods before versus during COVID-19, conservative approach was reported in 36.3% and 43.2% before versus during COVID-19, respectively, whereas surgical intervention was performed in 62.5% of patients before COVID-19 and 55.3% during the pandemic The length of stay was delayed when a non-surgical approach was selected in most studies. Complications, mainly classified by the Clavien-Dindo scale, were higher in the pandemic period. Conclusions: A tendency towards more conservative approaches was observed in most studies, reversing the previously used surgical approach in most cases of acute cholecystitis. In most of the examined cases during COVID-19 pandemic, antibiotic treatment as well as percutaneous cholecystostomy were much more considered and even preferred.